Current status of zirconia-based all-ceramic restorations fabricated by the digital veneering technique: a comprehensive review - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2019)
Objectives: Delamination and chipping are major complications of veneering material on zirconia-based all-ceramic restorations. The digital veneering technique was introduced to overcome these complications as both zirconia frameworks and veneering ceramic are fabricated by computer-aided design/computer-aided manufacturing (CAD/CAM). The aim of this review is to report all articles that evaluate zirconia-based all-ceramic restorations fabricated by the digital veneering technique. Three different digital veneering techniques were detected: the Lava DVS Digital Veneering System (3M ESPE), the Rapid Layer Technology (Vita Zahnfabrik), and the CAD-on technique (Ivoclar Vivadent). There are also some modifications of these techniques in the literature. Materials and methods: For this review, a comprehensive literature search was conducted. Detected studies are reported according to fracture resistance, flexural strength, wear performance, shear bond strength, microtensile bond strength, mechanical performance of restorations on implant abutments, marginal fit, color reproducibility, and clinical success for all types of digital veneering techniques. Results and conclusions: Anatomical framework design and digital veneering using lithium disilicate and fusion porcelain might decrease the risk of chipping and delamination of veneering ceramic on zirconia-supported all-ceramic restorations. However, this result is mainly supported by in vitro studies. More clinical studies with a large sample size, longer follow-up period, and different fixed dental prosthesis designs are needed.
Keywords: digital veneering; zirconia; CAD-on; rapid layer; sintering technique; FIXED DENTAL PROSTHESES; MICROTENSILE BOND STRENGTH; IN-VITRO PERFORMANCE; LITHIUM DISILICATE; FLEXURAL STRENGTH; FRACTURE-RESISTANCE; CHIPPING BEHAVIOR; CROWNS; RELIABILITY; FRAMEWORK